2019
DOI: 10.3390/cells8040326
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Concentrations Negatively Regulate the IGF1R/Src/ERK Axis through the MicroRNA-9 in Colorectal Cancer

Abstract: Studies have revealed that people with hyperglycemia have a high risk of colorectal cancer (CRC). Hyperglycemia may be responsible for supplying energy to CRC cells. However, the potential molecular mechanism for this association remains unclear. Furthermore, microRNA-9 (miR-9) has a tumor-suppressive function in CRC. Aberrant reduced expression of miR-9 is involved in the development and progression of malignancy caused by a high glucose (HG) concentration. In this study, we used an HG concentration to activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 65 publications
(74 reference statements)
2
12
0
Order By: Relevance
“…Matrigel invasion assays were performed to measure the invasive ability of different CRC cells ( Figure 3A). According to the results, SW480 cells had low invasive potential, and KM12SM cells had high invasive potential, which was consistent with previous results [21][22][23]. Intriguingly, Spearman's test analysis showed that the invasive potential of different CRC cell lines positively correlated with cellular miR-106b-3p expression (r = 0.79, P < 0.01).…”
Section: Mir-106b-3p Promotes Crc Cell Invasiveness Via Emt Initiatiosupporting
confidence: 90%
“…Matrigel invasion assays were performed to measure the invasive ability of different CRC cells ( Figure 3A). According to the results, SW480 cells had low invasive potential, and KM12SM cells had high invasive potential, which was consistent with previous results [21][22][23]. Intriguingly, Spearman's test analysis showed that the invasive potential of different CRC cell lines positively correlated with cellular miR-106b-3p expression (r = 0.79, P < 0.01).…”
Section: Mir-106b-3p Promotes Crc Cell Invasiveness Via Emt Initiatiosupporting
confidence: 90%
“…We also discovered that IGF1R expression decreased in the calluses of mouse fracture samples with injection of agomiR‐7025‐5p. Previous studies demonstrated that abnormal IGF1R expression plays an important role in the pathogenesis of acute lymphoblastic leukaemia, adrenocortical carcinoma, colorectal cancer and Ewing sarcoma . Thus, our findings indicate that the miR‐7025‐5p/IGF1R axis may play an important role in bone metabolism processes including osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 62%
“…IGF1R is a transmembrane receptor tyrosine kinase that promotes the progression and metastatic ability of GC [ 67 ]. It can inhibit the apoptosis of cancer cells through the activation of SRC and PI3K/AKT [ 68 , 69 ]. As a cytoplasmic protein tyrosine kinase, PTK2 can enhance cell motility, survival, and proliferation through effects on cancer cells and stromal cells in the tumor microenvironment [ 70 ].…”
Section: Discussionmentioning
confidence: 99%